Metacognitive strategies for developing complex geographical causal structures: An interventional study in the geography classroom - Heuzeroth, Johannes; Budke, Alexandra (European journal of investigation in health, psychology and education, 2021)
This article examines the impact of applied metacognition on the development of geographical causal structures by students in the geography classroom. For that, three different metacognitive strategies were designed: a. action plan, activating meta-knowledge prior to problem-solving and simultaneously visualizing action steps for dealing with the task (A); b. circular thinking (C), a loop-like, question-guided procedure applied during the problem-solving process that supports and controls content-related and linguistic cognition processes; c. reflexion (R), aiming at evaluating the effectivity and efficiency of applied problem-solving heuristics after the problem-solving process and developing strategies for dealing with future tasks. These strategies were statistically tested and assessed as to their effectiveness on the development of complex geographical causal structures via a quasi-experimental pre-posttest design. It can be shown that metacognitive strategies strongly affect students’ creation of causal structures, which depict a multitude of elements and relations at a high degree of interconnectedness, thus enabling a contentually and linguistically coherent representation of system-specific properties of the human-environment system. On the basis of the discussion of the results, it will be demonstrated that metacognitive strategies can provide a significant contribution to initiating systemic thinking-competences and what the implications might be on planning and teaching geography lessons. (Orig.).